Perlindungan Hukum Terhadap Rahasia Dagang Obat-Obatan Tradisional Atas Pemanfaatan Tanpa Hak dalam Sistem Hukum Hak Kekayaan Intelektual Indonesia - Siti Hamidah (Jurnal Media Justitia Nusantara, 2017)
Secret commerce Protection, be accepted by the community industry, but instead secret commerce protection is still not entirely accepted by traditional communities in which their relations are still based on traditional ties. Traditional medicines have long been "living" in a traditional society, is regarded as a valuable economic asset. Of an object that needs to be maintained became the object of economic value. Countries that feel has a wealth of cultural and natural resources began to see that the traditional medicine trade should be optimized in the competition at the international level. The topics that will be examined include, How is the Legal Protection of Traditional Medicine Trade Secrets for the use of without rights in the Indonesian Intellectual Property legal system? And how is the legal standing of the Trade Secret of Traditional Medicines in order to protect Indonesian Intellectual Property Rights. The method used in the study of law is normative, analytical descriptive. The study was conducted in one step, namely, library research to obtain secondary data in the form of primary legal materials and secondary law. Analysis of the data used is the juridical analysis of qualitative data is analyzed qualitative data obtained through literature searches and interviews of primary data, the data analysis is presented in the form of descriptions. The results of the study found that the Legal Protection of Intellectual Property Rights to the trade secrets of traditional medicines would not be able to be carried out either because it collided with the character of traditional knowledge that was mostly anonymous, communal (collective), did not contain novelty, was not written / documented and forever belongs to the community while the IPR system requires the opposite. Indonesia already has legislation in the field of intellectual property rights but its implementation is still questionable because various factors include law enforcement and the public who are unfamiliar with the legal aspects of protecting intellectual property rights.